Onchain Analysis: A Comparative Study of Decentralized Exchange (DEX) Activities on Ethereum, Solana, and Binance Smart Chain (BSC) - Dian Yusandika, Ajo; Hossain Bhuiyan, Alamgir; Sarothi Laskar, Partho (WISE Pendidikan Indonesia, 2025)
The rapid expansion of decentralized exchanges (DEXs) has reshaped cryptocurrency trading, yet comparative cross-chain evaluations remain scarce, particularly in transaction efficiency, liquidity sustainability, and economic viability. This study conducts an on-chain comparative analysis of Uniswap (Ethereum), Raydium (Solana), and PancakeSwap (BSC) by examining transaction count, trade volume, protocol revenue, and total value locked (TVL). Using real-time blockchain data from DefiLlama, Dune Analytics, Artemis, Token Terminal, and Arkham, this research applies quantitative cross-chain modeling to assess the performance of each ecosystem. Findings reveal that Ethereum leads in trade volume and liquidity depth, driven by institutional adoption despite high transaction costs. Solana exhibits superior transaction efficiency, attracting high-frequency traders, though its lower TVL suggests liquidity retention challenges. BSC, once a major DeFi player, now faces stagnation, with declining trade volume and fragmented liquidity. Unlike prior studies focusing solely on transaction metrics, this research integrates protocol revenue as a sustainability indicator, offering a broader understanding of DEX viability. The results underscore the need for cross-chain liquidity bridges and Layer-2 scaling solutions to mitigate liquidity fragmentation and enhance DeFi efficiency. This study contributes to both academia and industry by providing empirical insights for blockchain developers, investors, and policymakers, emphasizing the importance of scalability, liquidity incentives, and revenue optimization. The findings support future research on multi-chain liquidity integration, AI-driven market-making, and governance frameworks, guiding the next evolution of decentralized financial ecosystems.